Oho mauri : cultural identity, wellbeing, and tāngata whai ora/motuhake : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Māori Studies at Massey University, Wellington, Aotearoa/New Zealand - Pere, Lynne Mereana (Massey University, 2006)
This study, Oho Mauri, seeks to understand the experience of mental illness from the perspective of those it affects most- the consumer. In order to test the assumption that mental health depends as much on culture and identity as psycho-biology, Oho Mauri examines the worldviews of 17 Indigenous people – Māori - who have had experience of mental illness (Tāngata Whai Ora/Motuhake). Their views on mental illness, within the context of the recovery approach, constitute the core of the thesis. Oho Mauri examines the relationship between cultural identity and wellbeing, in order to answer the research question: "Does a secure cultural identity lead to improved wellbeing for Tāngata Whai Ora/Motuhake?” Indigenous people the world over have considered this relationship, generally maintaining that greater wellbeing is a function of ethnic values, customs, and practices. A methodological approach that is cognisant of Māori knowledge and understandings was key to this research. So too was the Kaupapa Māori research paradigm that was employed alongside other relevant qualitative methodologies: feminist, case study, empowerment, narrative, and phenomenological approaches. Two main sets of conclusions emerge from Oho Mauri, both of which are drawn from the cultural values and cultural worldviews that Tāngata Whai Ora/Motuhake hold. First, just as a secure cultural identity pays dividends in the recovery process, so can a cultural identity that has not been allowed to flourish increase the intensity of confusion and complexity that accompanies mental illness. Second, understanding mental illness has two dimensions: clinical; and personal. Whilst a diagnosis is a valuable clinical tool, understanding mental illness also requires recognition of the interpretations made by Tāngata Whai Ora/Motuhake and the meanings they attach to their personal experiences. Often these provide alternative explanations and understandings of the experience of mental illness and are perceived as the most significant aid in a journey towards recovery. The findings in Oho Mauri do not claim that a secure cultural identity will necessarily protect against mental illness. They do demonstrate, however, that cultural identity is an important factor in the recovery process and that the recovery process itself can contribute to a secure cultural identity.
Keywords: Maori mental health; Māori Doctoral Thesis; Fields of Research::370000 Studies in Human Society::379900 Other Studies In Human Society::379902 Indigenous studies